Actualization of Character Education Values in the Independent Curriculum at SMP Negeri 2 Bantaeng - Tenriwala, Tenriwala; Muhammad Azis; Elpisah, Elpisah (International Journal of Education, Vocational and Social Science, 2024)
This research aims to provide information regarding the actualization of character education values in the Independent Curriculum at SMP Negeri 2 Bantaeng and provide information regarding the implementation of the Independent Curriculum at SMP Negeri 2 Bantaeng. This type of research is descriptive qualitative field research. Meanwhile, data collection methods use data collection techniques, interviews, observation, questionnaires and documentation. Interviews were conducted with school principals, teachers and students. Observations, questionnaires and interviews were carried out to obtain direct information regarding physical and non-physical conditions regarding the outline of the actualization process of character education values in the Merdeka Curriculum at SMP Negeri 2 Bantaeng. Documentation is carried out to obtain documentary information regarding research. The research results show that the process of activities to actualize the values of character education in the Merdeka Curriculum at SMP Negeri 2 Bantaeng is based on habits that are carried out regularly, once a week, and some are carried out once a year. The Project Activity Strengthening the Pancasila Student Profile (P5) is a project-based co-curricular activity which aims to achieve learning competencies and student characteristics so that they are in accordance with the Pancasila Student Profile. P5 is developing the character of Indonesian students so that students become students who live the values of Pancasila. As the aim of implementing P5 in the Independent Curriculum is to become a Pancasila Student. The character values in the Merdeka Curriculum include faith, devotion to God Almighty, noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity. Based on the Independent Curriculum, the character values instilled in schools are religious values, discipline, cooperation, wisdom, innovation and responsibility. SMP Negeri 2 Bantaeng has used the Merdeka Curriculum by choosing 'Independent Change' as the implementation option in the Merdeka Curriculum